2022
DOI: 10.1016/j.prmcm.2021.100029
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic mechanisms and impact of traditional Chinese medicine on COVID-19 and other influenza diseases

Abstract: Coronavirus disease 2019 (COVID-19), first reported in Wuhan, China, has rapidly spread worldwide. Traditional Chinese medicine (TCM) has been used to prevent and treat viral epidemics and plagues for over 2,500 years. In the guidelines on fighting against COVID-19, the National Health Commission of the People's Republic of China has recommended certain TCM formulas, namely Jinhua Qinggan granule (JHQGG), Lianhua Qingwen granule (LHQWG), Qingfei Paidu decoction (QFPDD), Xuanfei Baidu granule (XFBD), Xuebijing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 100 publications
(134 reference statements)
0
7
0
Order By: Relevance
“…These immune cells overproduce cytokines like IL1, IL10, IL18, IFNα, and IL6 ( 152 , 153 ). In brief, COVID-19 coinfection with TB promotes cytokine storms that cause multiple organ injuries, particularly to the lungs, heart, or liver ( 5 , 150 , 151 ). These two pathogens induce cytokine storms with similar features but different magnitudes and outcomes.…”
Section: Impact Of Sars-cov-2 Pandemic On Tb Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…These immune cells overproduce cytokines like IL1, IL10, IL18, IFNα, and IL6 ( 152 , 153 ). In brief, COVID-19 coinfection with TB promotes cytokine storms that cause multiple organ injuries, particularly to the lungs, heart, or liver ( 5 , 150 , 151 ). These two pathogens induce cytokine storms with similar features but different magnitudes and outcomes.…”
Section: Impact Of Sars-cov-2 Pandemic On Tb Patientsmentioning
confidence: 99%
“…This unusual cytokine production may destroy host immune responses, i.e., low lymphocyte infiltration into infected lungs and multiple organ damage ( 192 ). Because SARS-CoV-2 is a novel CoV and has no specific treatment ( 5 ), suspected people must be tested accurately to prevent virus transmission. Apart from traditional diagnostic testing for detecting viral antigens or antiviral antibodies, the nucleic acid detection method has been developed for routine testing ( 193 ).…”
Section: Diagnostic Challenges and Management Of Covid-19-tb Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other 56 components were both anti-inflammatory and anti-SARS-CoV-2. Among these components, Quercetin, Wogonin, and Emodin were able to interfere with various stages of the coronavirus entry and replication cycle (59,81,82). Kaempferol could be used as an antiviral drug against the 3a Channel Protein of Coronavirus (55).…”
Section: Construction Of "Herb-active Component-target" Interaction N...mentioning
confidence: 99%
“…Accumulated clinical evidence shows that TCM has a significant positive impact on COVID‐19 patients, by reducing clinical symptoms, promoting recovery, improving chest images, and inhibiting disease progression [ 14 , 15 ]. Meanwhile, an increasing number of studies on therapeutic mechanisms have shown that TCM treatment not only targets the virus but also improves the whole body [ 16 , 17 , 18 , 19 ]. In addition, many natural products (NPs) and derivatives (such as Proscillaridin A, Scutellarein, Phillyrin, Quercetagetin, and Dihydromyricetin) from TCM herbs have been shown to exhibit activity against SARS‐Cov‐2 by in vitro assays and/or in silico methods (network pharmacology analysis, molecular docking, and virtual screening, etc.)…”
Section: Introductionmentioning
confidence: 99%